The Italian Dementia National Plan - Teresa Di Fiandra; Marco Canevelli; Alessandra Di Pucchio; Nicola Vanacore (Annali dell'Istituto Superiore di Sanità, 2015)
The Italian Dementia National Plan was formulated in October 2014 by the Italian Ministry of Health in close cooperation with the regions, the National Institute of Health and the three major national associations of patients and carers. The main purpose of this strategy was to provide directive indications for promoting and improving interventions in the dementia field, not limiting to specialist and therapeutic actions, but particularly focusing on the support of patients and families throughout the pathways of care. Four main objectives are indicated: 1) promote health- and social-care interventions and policies; 2) create/strengthen the integrated network of services for dementia based on an integrated approach; 3) implement strategies for promoting appropriateness and quality of care; and 4) improve the quality of life of persons with dementia and their families by supporting empowerment and stigma reduction. These objectives and the pertaining actions are described in the present paper.